Evaluation Study of the High Yielding Varieties Programme Report for the Kharif - 1967 - Planning Commission (Planning Commission, 1968)
During the Rabi season of 1965-66, the Programme Evaluation Organisation undertook in 54 development blocks a quick appraisal of the emergency food production drive. The PEO carried out a similar current evaluation of the intensive agricultural production schemes during the Khari season of 1966 slightly enlarging the areas of observation (74 development blocks). Both were in the nature of quick observational studies having the main focus on problems of planning, programming, coordination and implementation. It was considered desirable to carry out a more detailed investigation on the implementation as well as the impact of the intensive agricultural production schemes and the high yielding varieties programme during 1966-67.
Programme Evaluation Organisation Planning Commission Government of India
Programme Evaluation Organisation Planning Commission Government of India